Case Report: Thoracoscopic repair of a residual inferior sinus venosus-type defect with right lower pulmonary vein–inferior vena cava communication: intraoperative support using real-time 3D transesophageal echocardiography - Li, Tianzong; Luo, Yiran; Liang, Qin; Hu, Kui; Wang, Chao (Frontiers in Cardiovascular Medicine, 2025)
BackgroundResidual venous defects after atrial septal defect (ASD) repair may remain asymptomatic for years and can be misinterpreted as partial anomalous pulmonary venous return. Accurate intraoperative imaging is essential to confirm the anatomy and guide repair, particularly in minimally invasive surgery.Case presentationA 28-year-old woman with no cardiopulmonary symptoms was referred after an abnormal electrocardiographic findings during a routine physical examination. She had undergone ASD repair at age 3. Transthoracic echocardiography revealed right heart enlargement, severe tricuspid regurgitation, and a suspected communication between right lower pulmonary vein (RLPV) and inferior vena cava (IVC), later confirmed by cardiac CT. She underwent thoracoscopic repair with tricuspid annuloplasty. Real-time 3D transesophageal echocardiography (RT-3D TEE) was used as an intraoperative aid to confirm the location of the residual RLPV–IVC communication, to support the placement of guidewire and catheter, and to assist in post-repair assessment. The surgery was completed successfully with complications, and follow-up imaging showed complete resolution of the defect.ConclusionIn this case, RT-3D TEE provided effective intraoperative support during thoracoscopic cardiac surgery by enhancing spatial orientation and improving procedural confidence. While not essential in all cases, it may serve as a valuable assistant in anatomically complex or visually limited situations.